2022
DOI: 10.30892/gtg.43304-898
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Impact of Soil Erosion in the Embulatovka River Basin on the Development of Recreational Conditions of the Natural Resource State of the West Kazakhstan Region

Abstract: The article analyzes the impact of soil erosion in the Embulatovka River basin on the development of recreational conditions of the natural resource state of the West Kazakhstan region. The purpose of the work is to determine the process of washing out the soil of the river basin of the Embulatovka River for different types of agricultural land. The analysis of soil erosion in the Embulatovka River basin can serve as a basis for identifying and changing factors that negatively affect soil erosion, which will i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
(6 reference statements)
0
1
0
Order By: Relevance
“…Romania has an agricultural area of 13.5 million ha in 2022 (European Commission, 2023a) and number one in the number of farms active in 2020 (Eurostat Statistic Explained, 2023). The arable lands are estimated at 38%, the pastures occupy 27%, forest 8% and haymaking are 4% of the land (Ramazanova et al, 2022). A significant number of these active farms, respectively 91.8% or 3.1 million, were less than 5 ha.…”
Section: Introductionmentioning
confidence: 99%
“…Romania has an agricultural area of 13.5 million ha in 2022 (European Commission, 2023a) and number one in the number of farms active in 2020 (Eurostat Statistic Explained, 2023). The arable lands are estimated at 38%, the pastures occupy 27%, forest 8% and haymaking are 4% of the land (Ramazanova et al, 2022). A significant number of these active farms, respectively 91.8% or 3.1 million, were less than 5 ha.…”
Section: Introductionmentioning
confidence: 99%
“…The relevance of the topic is determined by the increasing demand for forest recreational resources of the West Kazakhstan region. As a result of long-term research , it was revealed that 630 species of vascular plants belonging to 72 families and 309 genera grow in the floodplain forests of the Ural River within the West Kazakhstan region (Ramazanova et al, 2022;Ramazanova et al, 2020). The largest families are Poaceae -72 species (11.4%), Asteracae -65 species (10.3%), Fabaceae -38 species (6.0%), Rosaceae -37 species (5.9), Lamiaceae -36 species (5.7%), Caryophyllaceae -35 species (5.6%), Brassicaceae -29 species (4.6%), Chenopodiaceae -25 species (4.0%), Apiaceae -24 species (3.8%), Liliaceae -24 species (3.8%), etc.…”
Section: Introductionmentioning
confidence: 99%